2021
DOI: 10.1021/acs.jchemed.1c00521
|View full text |Cite
|
Sign up to set email alerts
|

Case for Narrative Inquiry: Understanding the Experiences of Elena, A Historically Minoritized Graduate Student in Chemistry

Abstract: The following methodological research article offers a case for using narrative inquiry to understand qualitatively the experiences of historically minoritized (HM) graduate students in chemistry. The research article utilizes empirical data aimed at understanding how a chemistry graduate program professionally develops graduate students into chemists. The scope for the research article centers on the experiences of an HM graduate student pseudonymized as Elena. Data sources for this work consist of ethnograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This was followed by recent work from Clandinin and Rosiek (2019) which contends that while narrative inquiry begins with an individual’s experience, the approach also takes into account social and cultural contexts in order to deepen the analysis. As these debates continue, within the field of educational research, scholars (see Hu & Dai, 2021; Nardo, 2021) continue to utilize narrative inquiry to study student experiences and how these experiences contribute to the formation of aspirations and learning trajectories.…”
Section: The Development Of Narrative Inquiry As a Methodologymentioning
confidence: 99%
“…This was followed by recent work from Clandinin and Rosiek (2019) which contends that while narrative inquiry begins with an individual’s experience, the approach also takes into account social and cultural contexts in order to deepen the analysis. As these debates continue, within the field of educational research, scholars (see Hu & Dai, 2021; Nardo, 2021) continue to utilize narrative inquiry to study student experiences and how these experiences contribute to the formation of aspirations and learning trajectories.…”
Section: The Development Of Narrative Inquiry As a Methodologymentioning
confidence: 99%
“…We conducted a qualitative observational study using a narrative inquiry approach . We used semistructured interviews to elicit students’ experiences.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a qualitative observational study using a narrative inquiry approach. 33 We used semistructured interviews to elicit students' experiences. We created six openended prompts, and participants could respond freely.…”
Section: Methodsmentioning
confidence: 99%
“…The use of a story or narrative can increase engagement in a topic through humanization and by providing context for abstract concepts. The story for the CCI workshop is based on a battery malfunction, providing the students with a topical, real-world problem to solve. It has been reported that lithium-ion batteries can fail due to variances in the concentration of electrolytes as well as due to the introduction of contaminants .…”
Section: Workhop Developmentmentioning
confidence: 99%